Analysis on Pedestrian Arrivals and Delays at Pelican Crossings. - Perpustakaan UGM, i-lib ([Yogyakarta] : Program Magister Manajemen UGM, 2001)
Most pedestrian-vehicle conflicts and accidents occur at Pelican Crossings because pedestrians violate the Red-Man (RM) period. Research was conducted to investigate the reasons underlying their behaviour. In other word, this research aimed at answering the question of why pedestrians crossed the street at any time. The research was carried out at a very busy Pelican crossing in the UK. The data were collected through a combination of direct measurements and video recordings to get information on signal periods, pedestrian arrivals, pedestrian crossing times, pedestrian flows and pedestrian delays. It was found that pedestrians cross the street at any time, so that they involve in traffic conflicts or potential accidents, because they experience high signal-imposed pedestrian delays.